Research handbook on contemporary intangible cultural heritage : law and heritage - Waelde, Charlotte; Cummings, Catherine; Pavis, Mathilde; Enright, Helena (Edward Elgar Publishing, 2018)
This Research Handbook explores contemporary intangible cultural heritage (ICH) from the perspectives of both law and heritage. It questions, probes and interrogates many different aspects of contemporary ICH, including the definitions and legal frameworks designed to safeguard it. In doing so the Research Handbook highlights not only gaps and inconsistencies, but also questions the relevance of the legal framework as it applies to ICH itself. Each chapter is concerned with a different aspect of contemporary ICH, international treaties and the law, including the 2003 Convention for the Safeguarding of the Intangible Cultural Heritage. A diverse range of contemporary examples are explored, ranging from the local and global identity of migrant children, to language and the Berlin techno music scene. Taken collectively, and with its focus on 'contemporary' culture, this Research Handbook is a departure from the established discourse that tends to include some forms of heritage to the exclusion of others. The authors challenge the authority of existing legal instruments, expose their limitations and propose innovative ways in which contemporary forms of ICH can be safeguarded, whether via the law or other means. This innovative Research Handbook will be of great interest to academics researching the legal protection of ICH and the relationship between ICH, human rights, communities, identity and international trade. Those with an interest in the protection of a-typical intellectual property will also find this Research Handbook to be a source of valuable information.